Pharmacokinetic behavior of marbofloxacin in plasma from chickens at different seasons - Urzúa Pizarro, Natala Francisca (2017)
The purpose of this study was to evaluate the differences in the disposition and plasma pharmacokinetic behavior of marbofloxacin (MAR) in broiler chickens at different seasons. Chicken broilers (n = 345) were used, in lots of 5 individuals, divided into 6 groups depending on the way of administration, intravenous or oral (dose 2 mg/kg) and the test period. Post-administration plasma samples were obtained at different times, intravenously (0.08 to 24 hours) and orally (0.25 to 120 hours). A liquid-liquid extraction of MAR was performed by high-performance liquid chromatography (HPLC) with a fluorescent detector. The plasma concentrations obtained at the different sampling times of each season, were analyzed with ANOVA and pharmacokinetic analysis was conducted with the PK Solution 2.0 software. The concentration of marbofloxacin in plasma was significantly lower in winter and summer than in spring, with MAR being detected in winter up to 72 hours post-application, coinciding with the differences in MAR pharmacokinetics parameters with increase in the average residence time (MRT) is 9.4 hours in winter. Increased clearance MAR in summer (7.5 ml/min/kg) coincides with MRT 6.3 hours. Finally, the oral bioavailability of MAR is lower in summer and winter (86 ± 1.7% and 78 ± 3.1%) than in spring (94 ± 5.2 %). There are differences in the disposition and plasma pharmacokinetic behavior of MAR applied orally in broiler chickens, coinciding with the physiological changes in the thermoregulation of birds, considering its correct therapeutic management and contributing to provide safe food for human consumption.